Communicability Inspection: Which version of the Semiotic Inspection Method should I use? - Fortunato, Caíque B.; Costa, Ricardo B. C.; Prates, Raquel O. (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2025: Anais do XXIV Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais, 2025)
Introduction: The Semiotic Inspection Method (SIM) is widely used to evaluate the communicability of interactive systems, and over the years, researchers have proposed adaptations to SIM. Objective: This paper aims to identify and analyze proposals in the literature that generate a new version of the method. Methodology or Steps: A literature review was conducted to collect the intended studies. The new versions were then analyzed to understand their motivations and modifications proposed. Results: Five new versions of SIM were identified. The analysis reveals that different aspects of the method were altered according to the intended application context, reflecting the method’s flexibility and the evolving needs of its users.